Bacteria Isolated from Free-range Chicken (Gallus gallus domesticus) Eggs Sold in Semiarid Conditions and its One Health Impact - Sousa, Débora Luise Canuto de; Soares, Hannah Costa; de Medeiros, Katianny Bezerra; da Silva, Meire Maria; Bezerra, Camila Sousa; Alves, Clebert José; de Azevedo, Sérgio Santos; Santos, Carolina de Sousa Américo Batista (Acta Scientiae Veterinariae, 2021)
Background: Food contamination is an important and growing public health concern due to the risk of foodborne illnesses. In this context, the egg, consumed all over the world, stands out. This food has been pointed out as a carrier of several bacteria, causing outbreaks of food toxinfection. The production of free-range chicken eggs (Gallus gallusdomesticus) has been an alternative for generating income for producers in Brazil; however, there is no monitoring of the sanitary quality of this product. The objective of this study was to identify microorganisms in 128 free-range chicken eggs sold in open markets in the semiarid region of Northeastern Brazil. Discussion: The frequency of bacterial isolation obtained in this study was high and reflects contamination of the eggs, which can occur through the shell, and factors such as air humidity, time and temperature favor the migration of bacteria from the shell to the internal content of egg. Food toxinfection occurs due to improper conditions in food processing, and it is essential to guarantee correct handling, promoting health quality. Therefore, some care related to egg management is necessary, from primary production to commercialization, ensuring food safety for consumers. Another point to be highlighted concerns the way of marketing this product. Eggs from free-range chickens are usually sold in open markets, kept at room temperature from production to final distribution, mainly in the semiarid region of Northeastern Brazil. Temperature, storage time and chicken’s characteristics (lineage, age, nutritional management and health status) are factors that have a direct influence on the quality of the food offered to the consumer. The high frequency of isolated bacteria warns of the implementation of control measures to avoid contamination of this product and the importance of the correct use of antimicrobials in poultry, in order to avoid the spread of resistance-carrying pathogens, minimizing economic, health and environmental impacts.